Robust exponential attractors for singularly perturbed phase-field type equations - Alain Miranville; Sergey Zelik (Electronic Journal of Differential Equations, 2002)
In this article, we construct robust (i.e. lower and upper semicontinuous) exponential attractors for singularly perturbed phase-field type equations. Moreover, we obtain estimates for the symmetric distance between these exponential attractors and that of the limit Cahn-Hilliard equation in terms of the perturbation parameter. We can note that the continuity is obtained without time shifts as it is the case in previous results.